Характеристика генетической структуры селекционного поголовья крупного рогатого скота голштинской и белорусской черно-пестрой пород по гену пролактина (bPRL) - Михайлова, М.Е.; Белая, Е.В.; Тиханович, Н.И.; Хотляник, Н.В. (Фактори експериментальної еволюції організмів, 2013)
Aims. Estimate the frequency of alleles of prolactin gene in the two groups cattle of Holstein and black-and-white breed. Methods. The method of PCR-RFLP was used. Results. The frequencies of bPRL-RsaIА and bPRL-RsaIB alleles of prolactin gene were determined in the two groups cattle of Holstein and black-and-white breed. Conclusions. Evaluation of conformity observed genotype frequencies with expected genotype frequencies according to Hardy-Weinberg equilibrium. Found that the bPRL-RsaIB allele is a rare in both the studied group. The distribution of allele frequencies of prolactin gene in both populations did not differ. The observed genotype frequencies correspond to the theoretically expected by the Hardy-Weinberg equilibrium.